Attitudes Toward Money and Control Strategies of Financial Behavior: A Comparison Between Overindebted and Non-overindebted Consumers - de Almeida, Filipa; Ferreira, Mário B.; Soro, Jerônimo C.; Silva, Carla Sofia (Frontiers in Psychology, 2021)
This paper addresses whether overindebted and non-overindebted consumers differ in their attitude toward money (specifically, the degree to which consumers care about money and feel difficulties keeping track of their money) and how this attitude impacts three different financial behavior categories: record keeping (e.g., recording spending in writing), adjusting balance (e.g., trying to find ways to decrease one’s expenses to match income), and monitoring balance (e.g., monitoring one’s spending to see if it is in line with what is expected). Overindebted consumers were recruited via an NGO for consumer defense and were categorized (whenever possible) into two subgroups: consumers who became overindebted due to internal causes (e.g., bad financial management) and consumers who became overindebted due to external causes (e.g., unemployment). Non-overindebted consumers were a convenience sample. Non-overindebted consumers showed more positive attitudes toward money than both groups of overindebted consumers and overindebted due to external causes showed more positive attitudes than overindebted consumers due to internal causes. All groups share similar financial management behaviors except for monitoring balance, which was more frequent among non-overindebted consumers. Furthermore, a regression analysis indicates that money attitudes helped explain financial behavior differences between consumers above and beyond their indebtedness status. Consumers’ attitude predicted financial behaviors, even when controlling for relevant socioeconomic variables (education, income, age, and gender). Further analyses comparing money attitudes and financial behavior for the three subgroups (non-overindebted, overindebted due to internal causes, and overindebted due to external causes) showed no differences.